PEMBELAJARAN MATEMATIKA MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS MATERI SEGIEMPAT KELAS VII - Sayyidatul Karimah (Universitas Pekalongan, 2013)
Students experience in learning mathematics, they stated that the completion of word problems is more difficult than non-story. This happens because they are required to be able to understand , plan for completion and make a solution of the problem. Completion of word problems requires mathematical communication skills of each student . Therefore , teachers must be able to stimulate the students to improve communication skills by planning and implementing mathematical learning according to their condition. One type of cooperative learning is the CIRC , which emphasizes the ability to read or understand the problems. This research is a quantitative study using experimental methods . The variable in this study is a mathematical communication skills as independent variables and mathematical learning model with the CIRC as the dependent variable . The data were obtained by using the test . The data were processed with one sample t-test and test Normalized Gain . The results showed that the average mathematical communication skills achieved by students is 76.71 . This value exceeds the specified KKM (KKM = 70) so as to achieve mastery learning. The results of test calculations mathematical communication skills improvement based on pre-test and post- test was 35.12 % , which means an increased interpretation capabilities including mathematical communication in the medium category . Based on the results obtained , it is known that the mathematical learning by using cooperative learning model CIRC can improve students' mathematical communication skills .